Development of a Meat Tenderizer Based on Papaya Peel - Islam, Mir (Universidad Tecnológica de Panamá, Panamá, 2013)
Green papaya (Carica papaya L.) peels, obtained as a waste product in the processing of papaya pickles, were dried and their proteolytic activity was compared with that of the enzyme in the papaya latex. The proteolytic activity of the enzyme in papaya peel was about 10 times lower than that in the latex. Taking into account the activity of the enzyme, spice batches were mixed with 30% and 45% papaya peels, in order to formulate meat tenderizers. According to the sensory evaluation of the cooked samples, the meat marinated with 30% of green papaya peel, for 2 h at room temperature had the highest level of acceptance for its soft texture and good flavor. In conclusion, green papaya peel, dried, ground, and mixed with various spices showed a great potential for use as a low-cost meat tenderizer. Furthermore, the process described here allows the conversion of papaya peels with a negative value to an essential value added ingredient.